EVALUATION OF MUNGBEAN (VIGNA RADIATA L. WILCZEK) GENOTYPES IN WATERLOGGING ENVIRONMENT USING MULTIVARIATE TECHNIQUES - Islam, M Rafiqul (Journal of Agricultural Sciences (Belgrade), 2020)
Waterlogging is one of the major constraints of mungbean production in tropical and subtropical regions of the world and causing a significant yield loss. Therefore, this study aims at evaluating mungbean genotypes tolerant to waterlogging employing rigorous field screening procedures. About 3-weeks old seedlings of 100-mungbean genotypes were subjected to waterlogging for 3 days maintaining a waterlogging depth of 2.5 cm. A total of 18 plant characters were evaluated and compared under waterlogged and non-waterlogged situations during recovery period. It showed a wide range of variation among genotypes in relative plant characters. Most of the relative plant traits showed significant correlations with the seed yield but the relationships were much strong in waterlogged plants. The highly correlated nine relative plant characters were used in multivariate analyses for clustering the genotypes. The cluster 6 genotypes performed better in respect of almost all plant characters. Cluster 7 genotypes were also good whereas Cluster 4 genotypes performed poorly. Discriminant function analysis (DFA) showed that function 1 explained 54.5% and function 2 explained 32.2% and altogether 86.7% of the total variance in waterlogging tolerance. The harvest index and straw dry weight mostly explained the total variance in function 1. Root dry matter, shoot dry matter and also straw dry weight explained the maximum variance in function 2. Root dry matter played the most dominant role in explaining the maximum variance in the genotypes. The genotypes IPSA-10 and VC 6379 (23-11) performed better in respect of yield and associated morphological-physiological characters under waterlogging environment.